Multidimensional scaling analysis of virus diseases. Issue 131 (July 2016) - Lopes, António M.; Andrade, José P.; Tenreiro Machado, J.A.
Highlights: We review the quantitative and qualitative behaviour of 22 infectious diseases caused by viruses. The information is compared and visualized by means of Multidimensional Scaling technique. The results are consistent with clinical practice. The proposed mathematical tools tackle a large number of virus and information. Abstract: Background and Objective: Viruses are infectious agents that replicate inside organisms and reveal a plethora of distinct characteristics. Viral infections spread in many ways, but often have devastating consequences and represent a huge danger for public health. It is important to design statistical and computational techniques capable of handling the available data and highlighting the most important features. Methods: This paper reviews the quantitative and qualitative behaviour of 22 infectious diseases caused by viruses. The information is compared and visualized by means of the multidimensional scaling technique. Results: The results are robust to uncertainties in the data and revealed to be consistent with clinical practice. Conclusions: The paper shows that the proposed methodology may represent a solid mathematical tool to tackle a larger number of virus and additional information about these infectious agents.